The Effect of Fiscal Decentralization, Gross Regional Domestic Product, Education, And Unemployment Rate on Poverty Levels with ZIS Funds (Zakat, Infaq, and Shodaqoh) as Moderating Variables in Kebumen Regency in 2013-2023 - Affifa, Anis; Bawono, Anton (INCOME: Innovation of Economics and Management, 2024)
This research is to determine the effect of the variables fiscal decentralization, gross regional domestic product, education, unemployment rate on poverty levels with zakat funds (zakat, infaq, and shodaqoh) as moderating variables in Kebumen district in 2013-2023. This research is quantitative research with secondary data in the form of time series data. The data obtained was further processed with eviews12. In this analysis, descriptive tests, stationary tests, classical assumption tests, statistical tests and MRA tests are used. The results of this research conclude that the variables fiscal decentralization, gross regional domestic product, education, unemployment rate do not show any influence on the poverty level. ZIS funds are unable to moderate fiscal decentralization, gross regional domestic product, education, unemployment rates. As well as the variables fiscal decentralization, gross regional domestic product, education, unemployment rate were removed from the regression model to cure multicollinearity.